Knowledge of basic attention professionals about prevention and early detection of breast cancer in the state of Goiás - Rahal, Rosemar Macedo Sousa; Rodrigues, Danielle Cristina Netto; Corrêa, Rosangela Silveira; Soares, Leonardo Ribeiro; Ferreira, Sarah Hasimyan; Perillo, Pedro Henrique de Ávila; Almeida, Nilza Alves Marques (Mastology, 2021)
The role of Basic Health Care (BHC) professionals is essential in the primary and secondary prevention of breast cancer. The aim of this study was to characterize BHC professionals in the Health Regions of a federative unit and to assess their knowledge about breast cancer. This was a prospective study carried out with BHC professionals from the state of Goiás. Phase 1 – Preparation of material and training of the team. Phase 2 – Agreement of actions between executing team and coordination of health regions. Phase 3 – Presentation of project at the collegiate meeting. Phase 4 – Qualification of BHC professionals with different learning methods and application of questionnaires, evaluating the contribution of the action. A total of 1,133 professionals were included; mean age was 36.3 years, and they were predominantly women (87.6%), working as community health agents (59.2%) and at public service (76.3%). Only 53.8% of professionals identified the female sex as a risk factor for breast cancer, while 90% identified family history as an important factor for the development of the disease. Important changes in physical examination that can occur in patients with the disease, such as skin retraction, skin bulging and nipple injury, were mentioned as a risk factor only by 35.3%, 31.3% and 39.7%, respectively. BHC professionals who participated in the project had less than ten years of professional experience and significant restrictions of knowledge about primary and secondary prevention of breast cancer. They still experience difficulties in accessing mammography and specialized care.